Stamens enclosed by petals in Berchemia (Rhamnaceae): a unique mechanism for pollen presentation - Ma, Fang; Zhao, Qian; Tian, Xing; Fu, Yao-lei; Liu, Wen-zhe (Frontiers in Plant Science, 2025)
IntroductionPollen is usually presented by the anthers after maturity. However, in some plants, pollen is presented to pollinators on other floral structures (other than the anthers), or via particular expulsion mechanisms, resulting in secondary pollen presentation. The unusual petal morphology in Berchemia mediates pollen presentation, characterised by a combination of secondary pollen presentation and primary pollen presentation. However, the function, the role in reproduction, and the evolutionary significance of the unusual petals remain unclear.MethodsIn this study, we took Berchemia flavescens and Berchemia polyphylla var. leioclada as examples, and used field observations, semi-thin sections technology, scanning electron microscopy, and pollination ecology detection methods to explore the unique pollen presentation strategies, petal functions, and reproductive strategies in Berchemia.ResultsThis is a unique pollen presentation process mediated by petals. In the advanced bud stage, petals curl inward, enclosing the stamens. Following anther dehiscence, pollen is released into the petal tube, where the filament and cone-shaped anthers act as pistons, extruding pollen or pollen clumps through gaps at the petal tube apex (secondary pollen presentation). Subsequently, as the anthers emerge from the petal tube, residual pollen is directly presented to pollinators (primary pollen presentation).DiscussionIn Berchemia, the petals enclosing the stamens, effectively shield the pollen from extreme environmental conditions. The petal-stamen complex slow movement (first centrifugal, later centripetal) and pollen presentation in Berchemia suggest a unique reproductive strategy. This mechanism promotes outcrossing, minimizing interference between the pistil and stamens, and offers reproductive assurance by delayed self-pollination.